La adopción homoparental en Colombia : presupuestos jurídicos y análisis de la idoneidad mental (2018)
ABSTRACT: The Colombian Political Constitution of 1991 transformed the legal, political, social, and cultural reality; the principles of the social state of law, human dignity, pluralism, the best interests of the child, and equality, among others, constitute the normative framework for homo-parental adoption in Colombia; hence, the legal system is not a barrier to this type of adoption – on the contrary, it is a set of rules that protect the right of children to have a family, and the homosexual community to form it. In Colombia, homoparental adoption has caused reactions against based on arguments that question homosexuals’ mental suitability. For this reason, this article proposes that homosexuality is addressed through the parental competence term, i.e., is the ability to generate flexible and adaptive answers to rearing, articulated to attachment, subsequently reshaping the nature of inappropriate bonds and personality.